Microanalysis of deposited layers in the inner divertor of JET with ITER-like wall. (August 2017) - Zhou, Y.; Bergsåker, H.; Bykov, I.; Petersson, P.; Possnert, G.; Likonen, J.; Pettersson, J.; Koivuranta, S.; Widdowson, A.M.; ,
Highlights: Microanalysis of deposition and fuel retention at divertor surfaces has been extended to the horizontal surface of Tile 0 in JET. Samples from both first and second shutdown with JET-ILW had been analysed. Preferential deposition of deuterium was found in pits at the surface, either in initial pits at the W coated surface, or in local depressed areas formed by damage. Abstract: In JET with ITER-like wall, beryllium eroded in the main chamber is transported to the divertor and deposited mainly at the horizontal surfaces of tiles 1 and 0 (high field gap closure, HFGC). These surfaces are tungsten coated carbon fibre composite (CFC). Surface sampleswere collected following the plasma operations in 2011–2012 and 2013–2014 respectively. The surfaces, as well as polished cross sections of the deposited layers at the surfaces have been studied with micro ion beam analysis methods (µ-IBA).Deposition of Beand other impurities, and retention of D is microscopically inhomogeneous. Impurities and trapped deuterium accumulate preferentially in cracks, pits and depressed regions, and at the sides of large pits in the substrate (e.g. arc tracks where the W coating has been removed). With careful overlaying of µ-NRA elemental maps with optical microscopy images, it is possible to separate surface roughness effects from depth profiles at microscopically flat surface regions.